Surface mount technology principles and practice - Prasad, Ray P. (Chapman & Hall, 1997)
This edition continues to focus on educating the electronics engineer in surface mount principles, mainstream industry practices, and technology options. The author is a noted expert who is constantly in demand for training throughout the industry. The chapters are a walk-through of the actual assembly process. A new chapter discusses the effect of high pin count devices (fine pitch, BGA, and PGA) and their impact on board assembly. Practicing engineers will use the new appendix of vendors for components, sockets, material processes, and equipment. Expanded coverage of water soluble paste, no clean paste, and lead free solder addresses the environmental issues new to this industry.